Global antimicrobial use in livestock farming: an estimate for cattle, chickens, and pigs - Zahra Ardakani; Maurizio Aragrande; Massimo Canali (Animal, 2024)
Livestock farming substantially contributes to the global economy and food security. However, it poses crucial environmental, animal welfare, and public health challenges. The main objective of this study is to quantify the global antimicrobial use (AMU) in cattle, chicken, and pig farming. This information is important for understanding the potential impact of farm AMU on the emergence and spread of antimicrobial resistance among animals and humans. Using the United States Department of Agriculture Production, Supply, and Distribution and the Food and Agriculture Organization databases, we estimated the total supply of cattle (in heads) and its distribution into four weight categories: calves (26%), cows (41%), heifers (4%), and bulls of more than one year (29%). Similarly, we calculated the total supply of pigs (in heads) and divided it into two weight categories: pigs (96%) and sows (4%). For chickens, we considered one weight category. We attributed to each category a standard weight according to the parameters set by the European Medicines Agency (EMA) to determine the animal biomass at risk of antimicrobial treatment, or population correction unit (PCU). Finally, we estimated the global PCUs and then the global AMU based on the average administered to the three species (in mg of active ingredients per kg PCU). With this method, we estimated a global annual AMU of 76 060 tonnes of antimicrobial active ingredients (2019–2021 average), of which 40 697 tonnes (or 53.5%) for cattle, 4 243 tonnes (or 5.6%) for chickens, and 31 120 tonnes (or 40.9%) for pigs. According to our assessment, global AMU leads to almost 20 000 tonnes less than the previous estimates due to a different evaluation of PCUs. In previous studies, PCUs were calculated on the liveweight at slaughtering of animals, while our method considers the age and sex of animals and their average weight at treatment. Our results are consistent with the World Organization for Animal Health (WOAH) estimate of 76 704 tonnes of veterinary antimicrobials globally consumed in 2018 for the total of food-producing animals (the WOAH estimation is based on sales and import data).